Astigmatic treatment with photorefractive keratectomy: Investigations of non-keratometric ocular astigmatism - Peyman, A.; Dastborhan, Z.; Peyman, M. (Elsevier, 2017)
Purpose To evaluate the effect of non-keratometric ocular astigmatisms on visual and refractive outcomes after photorefractive keratectomy (PRK) for correction of myopic astigmatisms. Methods Seventy one eyes of 36 subjects were enrolled in this study. Patients underwent PRK for treatment of myopia. Subjects were evaluated for refractive error, keratometry, and visual acuity before and six months after surgery. Pre- and post-op non-keratometric astigmatisms were calculated by vectorial analysis of the difference between the corneal plane refractive astigmatism and keratometric astigmatism. Astigmatic analysis explored the contribution of non-keratometric astigmatisms. Results The pre-op spherical equivalent (SE) was −6.27 ± 1.48 with 1.16 ± 1.02 diopters of corneal plane refractive astigmatism and 1.44 ± 0.47 diopters keratometric astigmatism. Post-op values were −0.60 ± 0.85, 0.56 ± 0.47, and 1.06 ± 0.57, respectively, 6 months after surgery. Pre- and post-op non-keratometric astigmatisms were 0.76 ± 0.41 and 0.76 ± 0.46, respectively, (P = 0.976) with significant correlation (r = 0.37, P = 0.002). Pre-op non-keratometric astigmatisms correlated to the pre-op SE (r = −0.25, P = 0.04). Pre-op non-keratometric astigmatisms had significant correlation with keratometric difference vector of astigmatic correction (r = 0.369, P = 0.002). Post-op non-keratometric astigmatisms correlated to keratometric induced astigmatism (r = 0.334, P = 0.006), keratometric index of success (r = 0.571, P < 0.001), and post-op keratometric astigmatism (r = 0.736, P < 0.001). Conclusions Higher or lower non-keratometric ocular astigmatisms did not have any effect on refractive and visual outcome after PRK. PRK effectively corrected total refractive astigmatism through correction of keratometric astigmatism and additional adjustment to compensate for non-keratometric ocular astigmatisms.